2017
DOI: 10.3390/f8090342
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Causes of Land-Use and Land-Cover Change in Bannerghatta National Park: A Spatial Statistical Model

Abstract: Abstract:Land change modeling has become increasingly important in evaluating the unique driving factors and proximate causes that underlie a particular geographical location. In this article, a binary logistic regression analysis was employed to identify the factors influencing deforestation and simultaneous plantation driven reforestation in Bannerghatta National Park, located at the periphery of one of the fastest growing cities in India, i.e., Bangalore. Methodologically, this study explores the inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…[7][8][9]12,15,[18][19][20]23,28,29,33,35,37,40,41,45,49,[61][62][63]66,67,70,74,75,79 Geometric corrections include Orthorectification, Geo-referencing, Image Registration, ASCII Coordinate Conversion and Resampling. 1,7,13,16,[22][23][24][25][26]29,30,[32][33][34][35][36][37]40,[47][48][49]53,55,69,70,…”
Section: Pre-processing Techniquesmentioning
confidence: 99%
“…[7][8][9]12,15,[18][19][20]23,28,29,33,35,37,40,41,45,49,[61][62][63]66,67,70,74,75,79 Geometric corrections include Orthorectification, Geo-referencing, Image Registration, ASCII Coordinate Conversion and Resampling. 1,7,13,16,[22][23][24][25][26]29,30,[32][33][34][35][36][37]40,[47][48][49]53,55,69,70,…”
Section: Pre-processing Techniquesmentioning
confidence: 99%
“…All independent variables were standardized using the Z-score standardization method to reduce the disparities in scale of measurement and variance, because of different units of the variables. For these standardized variables, a multicollinearity test was conducted to avoid multicollinearity between independent variables by using the variance inflation factor (VIF) analysis [59]; variables with significant collinearity (VIF ≥ 10) must be removed from the LR model. These Z-score methods and multicollinearity analysis were performed in SPSS, and results shown that all independent variables were required to enter into LR model.…”
Section: Running Of the Lr Modelmentioning
confidence: 99%
“…Amongst these, the Wald statistic values are useful for judging the relative weights of each explanatory variable in a LR model, and they can be used to evaluate the contribution of each explanatory variable in event-prediction [17,25]. This means that higher Wald statistic values for an independent variable are the most important LUCC variables; these values have been widely used to assess the relative importance of each driving factor in such studies [10,17,59]. Variables in each LR model were therefore selected if they were statistically significant at a p-value less than 0.05, while Nagelkerke's R 2 values (between 0 and 1) in each logistic model were used to test the goodness of fit.…”
Section: Running Of the Lr Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the model can be easily implemented into GIS and RS, as it operates on lattice, raster-format geographic data, and consequently, it can work at high spatial resolution with computational efficiency [45]. In addition to its operational simplicity, it has the potential to simulate land-cover change with minimum data requirements [46]. This model has been widely used in many land-cover change simulations, for example, a case study in the Ashanti region (Ghana) based on the CA-Markov model showed an upsurge in built up area, and a decline in agricultural and forest land-cover [47].…”
Section: Land-cover Change and Demographic Dynamics In Conakrymentioning
confidence: 99%